Application of heavy metals environmental criteria on Amazonian continental shelf bottom sediments - de Lima, Edgar Alexandre Reis; Siqueira, Gilmar Wanzeller; de Lima, Waterloo Napoleão (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
The used criteria of environmental evaluation in this work, beyond the bioavailability, had been; the enrichment factor (x) and the geoaccumulation index (Igeo). The bioavailability of metals in the studied sediments showed, for some stations, anomalies, being its text many times superior to the concentrations in the total phase of the sediment. This happened, for example, for copper and manganese that, in certain points 40% exceeded, that is the limit suggested in the literature. Our also evidenced that only cobalt got classification considered ‘abnormal’ for the area (x>1 and Igeo=1), but it was characterized that metals are totally associated to its respective present minerals in the shelf.